Psychosocial work environment and risk of ischemic stroke and coronary heart disease: a prospective longitudinal study of 75 236 construction workers - Linus Schiöler; Mia Söderberg; Annika Rosengren; Bengt Järvholm; Kjell Torén (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: The present study aimed to investigate whether different dimensions of psychosocial stress, as measured by the job demand-control model (JDC), were associated with increased risks of ischemic stroke and coronary heart disease (CHD). METHODS: A cohort of 75 236 male construction workers was followed from 1989-2004. Exposure to psychosocial stress was determined by a questionnaire answered in 1989-1993. Events of ischemic stroke and CHD were found by linkage to the Swedish Causes of Death and National Patient registers. Hazard ratios (HR) were obtained from Cox regression models, adjusted for age, smoking habits, body mass index and systolic blood pressure. RESULTS: There were 1884 cases of CHD and 739 cases of ischemic stroke. Regarding ischemic stroke, no association was found between job demands [HR 1.12, 95% confidence interval (95% CI) 0.89-1.40, highest versus lowest quintile] or job control (HR 1.04, 95% CI 0.82-1.32, lowest versus highest quintile). Regarding CHD, job demands were associated to CHD (HR 1.18, 95% CI 1.02-1.37, highest vs. lowest quintile), but no consistent trend was seen among quintiles. The results were inconsistent in relation to job control. The division of JDC into four categories showed no significant associations with either ischemic stroke or CHD. CONCLUSIONS: This exploratory study showed no significant associations between psychosocial work environment and ischemic stroke, and the associations between job demands and control and CHD were inconsistent and weak. The combination of job control and job demand showed no significant associations with either ischemic stroke or CHD.